Evaluation of the Social Status of MGNREGA Women Beneficiaries in Uttarakhand State of India - Dr. Vinod Kumar (Journal of World Economy, 2023)
The term ‘status’ denotes position of an individual in a social system. It also encompasses the notions, rights and obligations of inferiority and superiority in terms of power, authority, rights and privileges when compared to that of man. Thus, it manifests her status in that particular society. When compared to man’s position, Indian woman always occupied a status, inferior to man, in all respects. Status includes not only personal and proprietary rights but also includes duties, liabilities and disabilities. With regard to the status of women in Indian society at large, no nation has held their women in higher esteem than the Hindus. The status of women in India has been subject to many great changes over the past few millennia. From equal status with men in ancient times through the low points of the medieval period, to the promotion of equal rights by many reformers, the history of women in India has been eventful. In modern India, women have adorned high offices in India including that of the President, Prime minister, Speaker of the Lok Sabha, Leader of Opposition, etc. The present research paper is the study of evaluation of the Social Status of MGNREGA Women beneficiaries in Uttarakhand State of India.